RELEVANSI PROGRAM MERDEKA BELAJAR PADA PEMBELAJARAN BAHASA INDONESIA BERBASIS LITERASI DI SMK KARYA SETIA PEGAJAHAN - Kirani, Dina; Putri, Rizka; Lubis, Lailan Syafira Putri (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2023)
The focus of this research is to find out the relevance of the Merdeka Belajar Program in Literacy-Based Indonesian Language Learning at SMK Karya Setia Pegajahan. This type of research is descriptive and qualitative. The subjects of this research were all students at SMK Karya Setia Pegajahan. Data analysis was used in this qualitative descriptive research by means of observation and interviews. The results of this study show that literacy skills are very important in the world of education. This is very much in accordance with the independent learning program that applies in Indonesia, which is learner-centered. Therefore, the author concludes that the independent learning program is very relevant to literacy-based Indonesian language learning at SMK Karya Setia Pegajahan.